Performance Evaluation of Ceramic Filters for Raw Water Treatment - Fahriza Fawwas Asrory; Agus Prasetya; Wahyu Wilopo (Indonesian Journal of Physics, 2020)
The drought that engulfs Gunungkidul every year forces some residents to use surface water resources in the lake or water sources in the cave even though the quality has not been tested. The application of ceramic filter technology as a household-scale water purification tool is a form of preventing further water contamination and reduces the level of the disease occurs due to the influence of biological and chemical contamination contained in water. This study aims to make ceramic filters and evaluate the performance of these filters by testing four parameters namely turbidity, hardness, E.coli, and Total Coliform. This study uses three filters, namely Pelita Indonesia (F1) production filter as a comparison filter, Kasongan Yogyakarta production filter with a composition of 80% (clay and sand) with a ratio of 1:1 and 20% wood sawdust with the addition of Silver Nitrate (AgNO3) ( F2), and Kasongan production filter with a composition of 100% clay mixed with sand without the addition of sawdust and Silver Nitrate (AgNO3) (F3). Sampling was carried out 15 times for 15 days by testing the water before and after going through the filtration process. The percentage reduction in the average for the turbidity parameter, (F1) was 38.24%, (F2) was 34.16%, and (F3) was 37.18%. The hardness parameter, (F1) is 22.22%, (F2) is 11.24%, and (F3) is 10.93%. The parameters of E.coli, (F1) are 100%, (F2) are 98.66%, and the filter with the composition of clay, sand (F3) is 46.71%. The Total Coliform (F1) parameter was 87.62%, (F2) was 69.38%, and (F3) was 51.32%. The application of ceramic filters can be done by looking at the ability of the filter to reduce the contamination contained in water. The addition of silver nitrate (AgNO3) must be done to reduce microbiological contamination.